Diagnostic Evaluation in Primary Intraocular Lymphoma : A Review - Desti Priani; Nabita Aulia (Universitas Negeri Gorontalo, 2022)
Background: Although very rare, there has been an increasing incidence of primary intraocular lymphoma (PIOL) in recent years. In addition, PIOL is often missed in diagnosis and is often treated without a standard, resulting in frequent recurrence and involvement of the central nervous system. Investigations have an important role in establishing the diagnosis of this case.Contents: The latest diagnostic supporting tests applied to PIOL are optical coherence tomography, fundus fluorescence angiography, indocyanine green angiography, fundal autofluorescence, ocular ultrasonography, vitrectomy sampling, and head MRI. Histopathological examination with Giemsa stain or hematoxylin-eosin is the gold standard in this case. Molecular studies and genetics have also recently played an important role in supporting PIOL diagnosis.Conclusion: PIOL has similarities with other vitreoretinal and uveal tract diseases, so it is not easy to diagnose. High clinical suspicion needs to be followed up with the latest investigations to establish PIOL diagnosis.